Morphophysiological characters of binahong (Anredera cordifolia (L.) Steenis) with application of natural growth regulators. Issue 4 (June 2021) - Mawarni, L; Hasanah, Y; Rusmarilin, H
Abstract: The morphophysiological study of binahong is still limited. The objective of the research is to identify the morphophysiological characteristics of binahong plants through natural GR application. This study described the relationship of plant length, number of leaves, stomatal density, and the content of chlorophyll leaves of binahong due to the application of natural growth regulators from coconut water combined with red shallot extract, bamboo shoots, and banana weevils. The research used a nonfactorial randomized block design with 3 replications. The results obtained in general giving GR can reduce plant length and number of leaves. The highest stomatal density was obtained in the application of coconut water while the lowest as shown in the application of coconut water and bamboo shoots. Chlorophyll a and b, as well as the highest total chlorophyll, are found without growth regulators application and application of a mixture of coconut water, shallot, bamboo shoots and, banana weevils. Chlorophyll a and b and the lowest total chlorophyll are found in the application of coconut water and bamboo shoots.